Highly sensitive and long-term stretchable eutectic nanogel conductor with conducting interpenetrating nanogel networks for monitoring human motions - Lim Jun Ho; KIM MIN JEONG; Ho Gyu, Yoon; Kim, Sang Woo (Pergamon Press Ltd., 2022)
As a stretchable e-skin for sensing repetitive and stressful body movements, we photo-polymerized choline chloride─acrylic acid (CA) deep eutectic solvents (DESs) with poly (3,4-ethylenedioxythiophene):poly (styrene sulfonate) (PEDOT:PSS), forming a choline chloride─acrylic acid─PEDOT:PSS (CAP) conductor with conducting interpenetrating nanogel networks. The CAP conductor is stretchable and self-healable due to ionic hydrogen bonding between the CA DESs and desulfurized PEDOT moieties. After treatment with sulfuric acid, structural rearrangement boosted the electrical conductivity of CAP by more than 100 times, achieving fast signal responses at high stretch─release rates and long-term anti-fatigue. Desulfurized CAP can realize a multifunctional smart wearable sensor.